Gender dan Permasalahannya Dalam Perspektif Islam - Ening Herniti (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
Women and men are educated and raised differently according to the perspective, social, and cultural backgrounds. These differences often result in gender inequality. Basically, Islam recognizes the differences between men and women, but not distinctions made in the physical - biological conditions of men and women. But keep in mind the differences are not necessarily a reason to glorify or demean one gender. Gender issues will give birth to a very complicated problem, among others, the problems of polygamy, reproductive health, hijab, language, leadership, and opportunities in education. Islam regards the strong fabric of society as between one individual and another individual. Men and women as part of the components of society, work together in achieving social balance. If one component of people experiencing injustice, social balance will not be realized automatically.